HUBUNGAN KADAR GULA DARAH DENGAN KADAR HbA1c PADA PASIEN DIABETES MELITUS TIPE II DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG TAHUN 2021 - Yuliza Birman; Intan Nur Harahap; Irwan Triansyah (Nusantara Hasana Journal, 2023)
Type 2 Diabetes Mellitus is a metabolic disorder characterized by increased blood glucose levels due to decreased insulin secretion from pancreatic beta cells or insulin resistance. Hyperglycemia in people with Diabetes Mellitus can cause complications such as heart attack, death, peripheral vascular disease. Examinations are needed that can control long-term blood sugar levels including checking blood sugar levels and HbA1c levels. Objective to determine the relationship between blood sugar levels and HbA1c levels in Type II Diabetes Mellitus patients at RSI Siti Rahmah Padang. This type of research is a cross sectional study. The affordable population in this study were Type II Diabetes Mellitus patients at RSI Siti Rahmah Padang in 2021. There were 67 samples using a simple random sampling technique. Univariate data analysis was presented in the form of a frequency distribution and bivariate analysis using the Kolmogorov-Smirnov test, data processing using computerization. The most gender was female, namely 37 people (55.2%), the most age was aged 56-65 years, namely 28 people (41.8%), the highest education level was high school, namely 33 people (49.3%), The most blood sugar levels were in the high category, namely 55 people (82.1%), the highest HbA1c levels were in the high category, namely 62 people (92.5%) and there was a relationship between blood sugar levels and HbA1c levels in Type 2 Diabetes Mellitus patients at RSI Siti Rahmah Padang (p=0.001). The most gender is female, the most age is 56-65 years, the most education level is high school, the most blood sugar levels are in the high category, the most HbA1c levels are in the high category, and there is a relationship between blood sugar levels and HbA1c levels in Diabetes Mellitus patients Type II at RSI Siti Rahmah Padang.